PHYTOCHEMICAL EVALUATION AND HIGH-PERFORMANCE THIN LAYER CHROMATOGRAPHY PROFILING: SAPINDUS EMARGINATUS VAHL. AND MORINDA PUBESCENS J.E.SM. BARKS EXTRACTS - Jedage HD; Kp, Manjunath (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To identify the flavonoids high-performance thin layer chromatography (HPTLC) profiles from barks of Sapindus emarginatus Vahl. (Sapindaceae) and Morinda pubescens J.E.Sm. (Rubiaceae) by ethanol extracts. Methods: The barks of S. emarginatus Vahl. and M. pubescens J.E.Sm. extracted each separately with ethanol. Both these ethanol extracts were subjected to preliminary phytochemical analysis. Based on phytochemical studies, the extracts obtained were subjected to HPTLC profiles for identify and confirmation flavonoids, both these samples were compared with standard (Rutin). HPTLC analysis performed with silica gel G 60 F254 plates with mobile phase ethyl acetate:n-butanol:formic acid:water (5:3:1:1). Detection of flavonoid compound was performed by scanning the developed plate at 254 nm. Results: Result of these both extracts shows positive tests for flavonoids. Ethanol extracts barks of S. emarginatus Vahl. and M. pubescens J.E.Sm each were showed bands of different Rf values with range 0.50-0.90 and standard showed bands of 0.50 Rf values. Conclusion: It can be concluded that rutin constituents of each bark extract are presents and have effective components which can be utilized as a useful herb for alleviation of various illness and disorders. Keywords: Sapindus emarginatus Vahl., Morinda pubescens J.E.Sm. Ethanol extracts, High-performance thin layer chromatography, Rutin.